2003
DOI: 10.1016/s0925-4773(02)00416-1
|View full text |Cite
|
Sign up to set email alerts
|

The OAR/aristaless domain of the homeodomain protein Cart1 has an attenuating role in vivo

Abstract: Aristaless-related genes encode a structurally defined group of homeoproteins that share a C-terminal stretch of amino acids known as the OAR- or aristaless domain. Many aristaless-related genes have been linked to major developmental functions, but the function of the aristaless domain itself is poorly understood. Expression and functional studies have shown that a subgroup of these genes, including Prx1, Prx2, Alx3, Alx4 and Cart1, is essential for correct morphogenesis of the limbs and cranium. We now demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…This does not seem to be the case for Alx3, because deletion of the region that contains the aristaless domain (Alx3-(1-279)) does not result in transcriptional enhancement in transfected cells, consistent with the notion that Alx3 contains a divergent aristaless domain that appears not to be functional (46).…”
Section: Proline-rich Domains Confer Transcriptional Transactivation mentioning
confidence: 81%
See 1 more Smart Citation
“…This does not seem to be the case for Alx3, because deletion of the region that contains the aristaless domain (Alx3-(1-279)) does not result in transcriptional enhancement in transfected cells, consistent with the notion that Alx3 contains a divergent aristaless domain that appears not to be functional (46).…”
Section: Proline-rich Domains Confer Transcriptional Transactivation mentioning
confidence: 81%
“…Proteins of this group bind preferentially to P3 sites as dimers in a cooperative manner, whereas binding to P5 sites occurs in monomeric form (22,47), a situation that has been confirmed for Alx4 and Cart1 (13,17,29,31). Alx3 has not been studied so extensively, but recently Brouwer et al (46) showed that binding of Alx3 to P3 is inhibited by the aristaless domain of Cart1, suggesting that sequences located outside the homeodomain can affect binding of aristaless-related proteins to their target DNA sites. Consistent with previous work on paired Q50 homeoproteins (22,29), our study shows that a segment of Alx3 spanning the homeodomain (Alx3-(143-228)) contains sufficient structural information for binding to P3 and P5 sites, and that monomeric binding to P5 is not sufficient for functional activity.…”
Section: Proline-rich Domains Confer Transcriptional Transactivation mentioning
confidence: 99%
“…5), we hypothesized that the precise control of the amount of Prrxl1 relative to Prrxl1-b is a key element in the regulation of the molecular mechanisms that govern the establishment of accurate sensory circuits. The importance of accurate regulation of the amount of this type of paired-like homeodomain transcription factors during development has been previously demonstrated by overexpression of an OAR truncated form of Cart1, which resulted in severe cranial and vertebral malformations due to an increase in DNA binding activity (Brouwer et al, 2003). We therefore suggest the existence of a delicate balance between Prrxl1 and its OARlacking variant, Prrxl1-b, which is critical during the nociceptive circuit development.…”
Section: Expression Of Prrxl1 Isoformsmentioning
confidence: 62%
“…Second, the OAR domain of Prx1a is likely involved in controlling chondrogenesis at the level of condensation. Several other paired-related homeoproteins, which have OAR domains, have been shown to have a role in chondrogenesis (Zhao et al, 1996;Heanue et al, 1997;Rao et al, 1997;Belo et al, 1998;Qu et al, 1998;ten Berge et al, 1998a;Rivera-Perez et al, 1999;Clement-Jones et al, 2000;Mavrogiannis et al, 2001;Ross et al, 2001;Brouwer et al, 2003). Within this group of OARcontaining proteins, a subset of genes classified as group I Aristaless, which include Prx2, Alx3, Alx4, and Cart1, are the most similar to Prx1a in terms of patterns of gene expression and sequence homology (Meijlink et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…Within this group of OARcontaining proteins, a subset of genes classified as group I Aristaless, which include Prx2, Alx3, Alx4, and Cart1, are the most similar to Prx1a in terms of patterns of gene expression and sequence homology (Meijlink et al, 1999;. Removal of the OAR domain in Cart1 was shown to increase DNA binding and transactivation potential in vitro in addition to producing ectopic cartilage in the mandible in vivo (Brouwer et al, 2003). Previous work from our lab has also shown that removal of the OAR domain of Prx1 and Prx2 increases DNA binding and transactivation potential (Norris and Kern, 2001a,b).…”
Section: Discussionmentioning
confidence: 99%